1986
DOI: 10.1111/j.1600-0714.1986.tb00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological distribution of phosphophoryn in normal and pathological human dentins

Abstract: Dentin phosphophoryn is a highly phosphorylated protein which has a hydrophilic character but is not soluble in dilute acetic acid. A histochemical method was developed for staining this protein with Stains‐all® in situ utilizing those chemical properties. We have succeeded in detecting the presence of this protein in circumpulpal orthodentin of human permanent and deciduous teeth, but not in mantle dentin, secondary dentin and reparative dentin. Phosphophoryn staining was also absent in the dentin of dentinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 25 publications
2
29
1
Order By: Relevance
“…DSP is a glycoprotein also present in dentin in low but measurable quantities (5-7). As early as 1988 it was suggested that mutations to the "dentin" phosphophoryn (sic) gene locus were a causative factor in DI-II (8,9). DI-II has been mapped to 4q21-q23 by linkage studies (10), which are consistent with the mapping of the human DSPP gene locus to chromosome 4q21.3 (4).…”
mentioning
confidence: 77%
“…DSP is a glycoprotein also present in dentin in low but measurable quantities (5-7). As early as 1988 it was suggested that mutations to the "dentin" phosphophoryn (sic) gene locus were a causative factor in DI-II (8,9). DI-II has been mapped to 4q21-q23 by linkage studies (10), which are consistent with the mapping of the human DSPP gene locus to chromosome 4q21.3 (4).…”
mentioning
confidence: 77%
“…In rat teeth, Gla proteins of the osteocalcin type can be demonstrated by immunostaining in newly differentiated odontoblasts as well as in predentin before initiation of mineralization (Bronckers etal., 1987;Gorter de Vries etal., 1987); the staining in mantle dentin is reportedly restricted to mineralized globular patches (Camarda et al, 1987). Also dentin phosphoprotein seems to be absent from mantle dentin (Nakamura et al, 1985;Takagi and Sasaki, 1986;Rahima et al, 1988).…”
Section: Cellsmentioning
confidence: 98%
“…8B shows the ion distributions in coronal molar dentin after demineralization with 0.5 M acetic acid for 1 h in the presence of cross-linking fixative. This acetic acid etching treatment was used for demineralization preparatory to immunohistochemical localization of the dentin noncollagenous protein-phosphophoryn (Rahima et al, 1988) and relied on the fact that phosphophoryn is not readily soluble in acetic acid (Butler et al, 1972;Takagi and Sasaki, 1986) as well as the cross-linking insolubilization of the proteins by the glutaraldehyde and formaldehyde. The total positive ion image presented in Fig.…”
Section: Demineralizationmentioning
confidence: 99%